(untitled) (Dandao Xuebao/Journal of Ballistics, 2023)
In order to develop a kind of controllable spin-stabilized projectile with stronger correction ability, a kind of spin-stabilized projectile with micro spoiler control mechanism was studied. The control principle of this kind of controlled projectile was analyzed. Aiming at its dynamic modeling problem, the mathematical model of the control force and the control torque of the spin-stabilized projectile with spoiler was established by considering the aerodynamic asymmetry. According to the six degree of freedom trajectory model, the effects of the spoiler height, projectile angle, initial velocity and start-up and control time on the stability and correction ability of the projectile were analyzed. The results show that the higher the spoiler height is, the stronger the correction ability is, but the more obvious the speed drop. The larger the oscillation amplitude and stability value of the attack angle are, the earlier the start-up and control time is. When the velocity changes from subsonic to supersonic, the correction ability first decreases and then increases.